2017
DOI: 10.1007/s12298-017-0426-y
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA dynamics in a wild and cultivated species of Convolvulaceae exposed to drought stress

Abstract: Agricultural productivity is severely hampered by drought in many parts of the globe. It is well-known that wild plant species can tolerate drought better when compared with their closely related cultivated plant species. Better drought adaptation of wild species over cultivated ones is accounted for their ability to differentially regulate gene expression. miRNAs, known to regulate gene expression at the post-transcriptional level, are admitted to play an important role in plant adaptation to stresses. This s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 62 publications
(64 reference statements)
1
9
0
Order By: Relevance
“…mtr-miR398a-5p is an important member of the miR398 family. The miR398 family in Medicago sativa was up-regulated under drought stress, and resembled the results found in Convolvulaceae, Medicago truncatula, and Jacquemontia pentantha [62][63][64], but differed from the results reported in Ipomoea campanulata [65]. Previous studies have shown that miR398 was crucial for plant stress responses, as it regulates copper-zinc superoxide dismutase (CuZnSOD) levels [66].…”
Section: Discussionsupporting
confidence: 59%
“…mtr-miR398a-5p is an important member of the miR398 family. The miR398 family in Medicago sativa was up-regulated under drought stress, and resembled the results found in Convolvulaceae, Medicago truncatula, and Jacquemontia pentantha [62][63][64], but differed from the results reported in Ipomoea campanulata [65]. Previous studies have shown that miR398 was crucial for plant stress responses, as it regulates copper-zinc superoxide dismutase (CuZnSOD) levels [66].…”
Section: Discussionsupporting
confidence: 59%
“…These four lncRNAs potentially interact with a miRNA by forming an lncRNA-miRNA duplex, which functions as RNA interference (RNAi), and as a result, miRNA-targeted mRNA is normally translated into a functional protein [ 32 ]. MiR403 has been reported to be involved in plant drought [ 73 – 75 ], heat, salt and cadmium stress response in a tissue associated manner [ 73 ]. Additionally, miR403 has an antiviral role by controlling the expression of AGO2 (Argonaute 2) [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been determined that miR394 mainly regulates the richness of the F-box domain proteins [50]. Previous studies have shown that when plants had suffered adversity stresses—such as B. cinerea , blue light, drought, and so on—the miR394 were downregulated in tomato [51], longan [52], wild Ipomoea campanulata L [53], and Saccharum spp . [54].…”
Section: Discussionmentioning
confidence: 99%